Adaptive Education Marketing Strategies to Increase Public Trust in The 5.0 Era - Rofiki, Moh.; Khoir, Nadia Kholifatur; Latifah, Saadul (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyze the adaptive education marketing strategy implemented by Mambaul Ulum Sukodadi Paiton Vocational High School in increasing public trust in the Society 5.0 era. This study uses a qualitative approach with a case study design, conducted through in-depth interviews, observation, and documentation. The results show that the adaptive marketing strategy at Mambaul Ulum Vocational High School covers three main aspects: the implementation of digital and participatory strategies, increasing public trust through proving the quality of graduates and social involvement, and integrating marketing values into the curriculum and learning process. The school utilizes the strength of its alumni, digital technology, and its identity as a pesantren as strategic attractions and differentiators. The innovative integration of marketing into education aims to develop students who are not only technically competent but also confident in presenting and marketing their work. These findings make an important contribution to the development of value-based, technology-based, and sustainable education marketing strategies in the 5.0 era.